Safety and immunomodulatory efficacy of heat-killed Mycolicibacterium manresensis as a novel paraprobiotic in swine - Álvarez-Delgado, Carmen; Ruedas-Torres, Inés; Sánchez-Carvajal, José M.; Fristiková, Karola; Rodríguez-Ruiz, Macarena; Larenas-Muñoz, Fernanda; Cerón, José J.; Pallarés, Francisco J.; Cardona, Pere J.; Rodríguez-Gómez, Irene M.; Carrasco, Librado; Gómez-Laguna, Jaime (Frontiers in Veterinary Science, 2025)
Given the increasing global concern about antimicrobial resistance, it is necessary to identify nutritional alternatives to antibiotics and trace elements in the porcine industry. The present study was carried out to evaluate the safety and effect of the paraprobiotic heat-killed Mycolicibacterium manresensis (hkMm) in weaned piglets. For this purpose, twenty-four-week-old piglets, were assigned to four experimental groups, and the diet of three of them was supplemented with 10, 50 and 100 ppm of hkMm, respectively, during a period of 70 d. Animals were monitored throughout the experiment, and weight data, blood, serum and saliva samples were collected every 2 weeks. At the end of the study, tissue samples were collected for histopathology, histomorphometry, immunohistochemical, and gene expression analyses. Supplemented animals did not show any adverse effects neither significant changes in their production parameters. Piglets supplemented with higher doses of hkMm exhibited a significant increase in salivary adenosine deaminase levels (p = 0.0042), along with a significant decrease in serum haptoglobin concentration (p = 0.0263). HkMm also appeared to induce a mild increase in circulating leukocyte populations at the end of the study, primarily due to elevated neutrophil counts, with smaller increases in lymphocytes and monocytes. Additionally, treated animals showed an increase in the number of regulatory T cells (FOXP3⁺) by immunohistochemistry, along with an increased IFNG response by RT-qPCR. Flow cytometry analysis in PBMC showed a decrease in the frequency of CD8β+ T cells (p = 0.0021), together with a higher number of γδ+ T cells in the treated animals throughout the study (p = 0.0327). On the other hand, histomorphometry analysis revealed a significant increase in mucosal height (p = 0.0195) and crypt depth (p = 0.0277) in the intestine of piglets receiving higher doses of hkMm. These results indicate that hkMm is a safe paraprobiotic with immunomodulatory potential, capable of enhancing intestinal integrity and absorptive capacity in weaned piglets, supporting its potential as a nutritional strategy to enhance gut health and reduce reliance on antimicrobial agents. Nevertheless, further studies in animals subjected to a challenge would be valuable to assess hkMm’s efficacy under immunological stress.